Methods in Modern Biophysics - Nolting, Bengt (Springer, 2006)
"Incorporating recent dramatic advances, this textbook presents a fresh and timely introduction to modern biophysical methods. An array of new, faster and higher-power biophysical methods now enables scientists to examine the mysteries of life at a molecular level. This text surveys and explains the ten key biophysical methods, including those related to biophysical nanotechnology, scanning probe microscopy, X-ray crystallography, ion mobility spectrometry, mass spectrometry, proteomics, and protein folding and structure. Incorporating much information previously unavailable in tutorial form, Bengt Nolting employs worked examples and 267 illustrations to fully detail the techniques and their underlying mechanisms. Methods in Modern Biophysics is written for advanced undergraduate and graduate students, postdocs, researchers, lecturers and professors in biophysics, biochemistry and related fields."--Jacket.